Stability Enhancement And Network Complexity Reduction In Minimal Resource Allocation Network And Probalistic Neural Network For Sonar Target Differentiation - Lim, Way Soong (2006)
This research is exclusively devoted to the performance investigation of minimal Resource Allocation Network (MRAN) and Probabilistic Neural Network (PNN) with regard to their prediction stability and network complexity reduction in sonar target differentiation.